Fabrication and properties of porous boron nitride/silicon oxynitride ceramic composites via gas pressure sintering. (15th December 2015) - Lin, Shaojie; Ye, Feng; Ma, Jie; Ding, Junjie; Liu, Qiang; Dong, Shangli
Abstract: Silicon oxynitride (Si2 N2 O) based wave transparent composites with different volumes of hexagonal boron nitride (h-BN) were prepared by gas pressure sintering at 1700 °C with 5.0–10.0 mol% Li2 O as additive. The effects of Li2 O and BN contents on phase, microstructure, mechanical and dielectric properties of the composites were investigated. The decomposition of Si2 N2 O and pore structures was influenced by Li2 O content, while the incorporation of h-BN effectively alleviated Si2 N2 O decomposition. The BN/Si2 N2 O composites could withstand a thermal shock of 1100 °C without strength degradation in N2, while only the samples with adequate porosity exhibited high thermal shock resistance in air. The high thermal shock resistance was attributed to the crack-healing ability of the composites. The as-sintered BN/Si2 N2 O ceramics showed both low dielectric constant (ε < 4.49) and loss tangent (tanδ < 0.0056) with good mechanical properties and thermal shock resistance, indicating that the as-sintered BN/Si2 N2 O composites could be used as promising high temperature wave transparent material. Graphical abstract: The pore structure could be modified by controlling the degree of Si2 N2 O decomposition, and the increase of Li2 O accelerated the decomposition. The oxidation derived borosilicate glass sealed the pores on the surface and protect the crystals beneath from oxidation damage, thus the thermal shock resistance was enhanced. Highlights: Pore structure was modified by controlling the degree of Si2 N2 O decomposition. Li2 O accelerates the Si2 N2 O decomposition while BN alleviates it. Borosilicate glass seals the surface and protects the crystals from oxidation damage. One of the samples could resist a thermal shock of 1300 °C in air atmosphere. The composites exhibit both good mechanical properties and dielectric properties.